TOPical Imiquimod treatment of high-grade Cervical intraepithelial neoplasia (TOPIC trial): study protocol for a randomized controlled trial. Issue 1 (December 2016) - Koeneman, M.; Kruse, A.; Kooreman, L.; zur Hausen, A.; Hopman, A.; Sep, S.; Van Gorp, T.; Slangen, B.; van Beekhuizen, H.; van de Sande, M.; Gerestein, C.; Nijman, H.; et al.
Abstract Background Cervical intraepithelial neoplasia (CIN) is the premalignant condition of cervical cancer. Whereas not all high grade CIN lesions progress to cervical cancer, the natural history and risk of progression of individual lesions remain unpredictable. Therefore, high-grade CIN is currently treated by surgical excision: large loop excision of the transformation zone (LLETZ). This procedure has potential complications, such as acute haemorrhage, prolonged bleeding, infection and preterm birth in subsequent pregnancies. These complications could be prevented by development of a non-invasive treatment modality, such as topical imiquimod treatment. The primary study objective is to investigate the efficacy of topical imiquimod 5 % cream for the treatment of high-grade CIN and to develop a biomarker profile to predict clinical response to imiquimod treatment. Secondary study objectives are to assess treatment side-effects, disease recurrence and quality of life during and after different treatment modalities. Methods/design The study design is a randomized controlled trial. One hundred forty women with a histological diagnosis of high-grade CIN (CIN 2–3) will be randomized into two arms: imiquimod treatment during 16 weeks (experimental arm) or immediate LLETZ (standard care arm). Treatment efficacy will be evaluated by colposcopy with diagnostic biopsies at 20 weeks for the experimental arm. Successful imiquimod treatment is defined as regression to CIN 1 or less, successful LLETZ treatment is defined as PAP 1 after 6 months. Disease recurrence will be evaluated by cytology at 6, 12 and 24 months after treatment. Side-effects will be evaluated using a standardized report form. Quality of life will be evaluated using validated questionnaires at baseline, 20 weeks and 1 year after treatment. Biomarkers, reflecting both host and viral factors in the pathophysiology of CIN, will be tested at baseline with the aim of developing a predictive biomarker profile for the clinical response to imiquimod treatment. Discussion Treatment of high-grade CIN lesions with imiquimod in a selected patient population may diminish complications as a result of surgical intervention. More knowledge on treatment efficacy, side effects and long-term recurrence rates after treatment is necessary. Trial registration EU Clinical Trials RegisterEU-CTR2013-001260-34 . Registered 18 March 2013. Medical Ethical Committee approval number: NL44336.068.13 (Medical Ethical Committee Maastricht University Hospital, University of Maastricht). Affiliation: Maastricht University Hospital. Registration number ClinicalTrials.gov: NCT02329171.